2015
DOI: 10.1007/s10552-015-0612-6
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent dietary vitamin D and sun exposure in relation to benign breast disease

Abstract: Purpose Vitamin D may reduce cell proliferation and tumor growth in breast tissue, and exposure may be most important during adolescence when breast tissue is developing. In the Nurses’ Health Study II, higher recalled adolescent vitamin D intake was associated with a lower risk of benign breast disease (BBD). Our study aim was to assess adolescent vitamin D exposure in relation to BBD in young women. Methods Vitamin D was assessed in 6,593 adolescent girls (9 to 15 years of age at baseline) in the prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Biological and epidemiological data have revealed the protective functions of vitamin D against different cancers especially breast cancer ( 13 - 15 ) and the potential role of VDR gene polymorphisms and risk of cancer ( 16 - 18 ). Interestingly, it was found that people with higher vitamin D levels have shown reduced incidence of breast cancer ( 19 , 20 ).…”
Section: Contextmentioning
confidence: 99%
“…Biological and epidemiological data have revealed the protective functions of vitamin D against different cancers especially breast cancer ( 13 - 15 ) and the potential role of VDR gene polymorphisms and risk of cancer ( 16 - 18 ). Interestingly, it was found that people with higher vitamin D levels have shown reduced incidence of breast cancer ( 19 , 20 ).…”
Section: Contextmentioning
confidence: 99%
“…Vitamin D binds to and activates the nuclear VDR which regulates as much as 3% to 5% of the human genome (Oh et al, 2007). Interestingly, it was found that people with higher vitamin D levels have shown reduced incidence of breast cancer (Garland et al, 2009 andBoeke et al, 2015).Among Egyptian women,vitamin D deficiency was identified in middle-aged, postmenopausal and geriatric women (Botros et al, 2015). According to De Lyra et al (2006) suboptimal vitamin D levels might lead to cancer development through impairment of cell proliferation, differentiation, apoptosis, and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of vitamin D, long-known for its crucial role in calcium homeostasis, and bone metabolism, is better understood recently by subsequent publication of several studies demonstrating the association of vitamin D levels with many organ cancers, heart disease, diabetes mellitus, and fertility rates 14,15 . It has long been speculated that vitamin D deficiency would accelerate the cellular proliferation of breast tissue in women and lead to the formation of breast masses 16 . Garland et al demonstrated a relation between serum vitamin D levels and breast cancer in 2007 which accelerated the studies on this subject subsequently.…”
Section: Introductionmentioning
confidence: 99%